Pentingnya Pengembangan Manajemen Dan Legalitas Usaha “Jahe Merah Omar” Asli Bangka - Manurung, Novela Debora; Diana, Nana (Jurnal Ilmiah Wahana Pendidikan, 2024)
Business legality is a standard that must be met by business actors. Businesses need legality not without purpose, but to get legal protection in their business, to increase the value of the company and to prevent losses from unwanted things. Business legality must be in accordance with laws and regulations so that businesses owned are protected through documents that are legal in the eyes of the law. Business actors must have business legality such as having a Business Identification Number (NIB), being registered with P-IRT, having halal certificates, having brand certificates, and so on to make it easier for business actors to run their businesses and be able to develop their marketing through e-commerce. Omar's Red Ginger business has been established since 2018. At the beginning this business did not have legality and had not developed management in the business so that sales were small and not recognized by the wider community. Then, in 2022 the owner of the Red Ginger business, Omar, begins to legalize his business and develop management in his business so that sales increase and his business grows rapidly.